Drainage of Complex Walled-Off Pancreatic Fluid Collections in LAMS Era: A Multicenter Study - Thanawat Luangsukrerk; Kamin Harinwan; Stanley Khoo; Pradermchai Kongkam (Canadian Journal of Gastroenterology and Hepatology)
Background. The lumen-apposing metal stent (LAMS) has been increasingly used for EUS-guided drainage of symptomatic walled-off pancreatic fluid collection (WOPFC) in recent years. Nevertheless, some WOPFCs may require additional drainage methods including another LAMS as a result of complexity of the lesions. This current study aimed to compare clinical parameters of patients with complex WOPFC requiring LAMS with additional methods (complex WOPFC: group A) versus single LAMS alone (noncomplex WOPFC; group B). Method. Medical records of patients with complex (group A) versus noncomplex WOPFCs (group B) were reviewed and compared in three centers in Thailand and Malaysia, between January 2016 to December 2020. Result. 31 patients with WOPFCs were recruited. 6 of 31 (19%) patients were in group A. Multivariate analysis showed that the maximal diameter of WOPFCs in group A was significantly larger than that of group B (18 ± 6 versus 13 ± 3 cm in diameter, respectively, p = 0.021). Solid component proportion was higher in group A versus B (35.8% versus 17.8%, respectively, p = 0.025). The prevalence of pancreatic duct leakage was significantly higher in group A (67% versus 20%, p = 0.23). The need of direct endoscopic necrosectomy (DEN) and the number of DEN sessions were higher in group A versus B (100% vs. 48%, p = 0.020 and 3.5 vs 0 p = 0.031, respectively). Conclusions. Complex WOPFC had larger diameter of lesions, higher proportion of solid component, higher prevalence of pancreatic duct leakage, and higher number of DEN is required than group noncomplex lesions. Trial Registration. This trial is registered with TCTR20180223004.